The analysis of power curves of wind power plants - A. A. Belsky; A. I. Zamyatin (Омский научный вестник)
The use of wind power plants is growing rapidly, despite the continued growth in the extraction of traditional fossil resources. In this paper, the analysis of the power curves of real wind turbine models and the polynomials common among the scientific community describing the dependence of the wind turbine output power on wind is carried out. The article discusses 82 models of wind power plants with a horizontal axis of rotation, rated power up to 100 kW and with a method of limiting the speed of rotation in the operating mode pitch control. The calculation of the potential generation of each wind turbine at an oil and gas field for a period of twenty years with an interval of one hour is carried out, the Installed Capacity Utilization Factor is calculated, after which the values are compared with the results of calculations based on polynomials of other authors. The results obtained can be widely applied in modeling the operating modes of wind power plants and will improve the accuracy of feasibility studies for the implementation of autonomous power supply systems.